2016
DOI: 10.18203/2320-6012.ijrms20161805
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between vitamin D and lipid profile in patients with ischemic stroke

Abstract: INTRODUCTIONExposure to sunlight and taking food rich in vitamin D can meet our daily requirements.1,2 Low serum levels of 25-hydroxyvitamin D (25(OH)D) is also shown to be associated with insulin resistance. 3,4 Vitamin D insufficiency has been linked to cardiovascular diseases, infections and even cancer in recent large epidemiological studies.5 Rise in serum cholesterol is associated with increase in cardiovascular diseases. 6,7 Studies have also demonstrated that 25-hydroxyvitamin D deficiency is a novel C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…Similar results were reported by various authors in their studies (11,12,13) . Wang et al also showed that raised levels of vitamin D were related with favorable lipid profile, whereas lower levels of vitamin D were related with atherogenic lipid profile (4) .…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were reported by various authors in their studies (11,12,13) . Wang et al also showed that raised levels of vitamin D were related with favorable lipid profile, whereas lower levels of vitamin D were related with atherogenic lipid profile (4) .…”
Section: Discussionsupporting
confidence: 92%
“…The present results identify a few micronutrients with the possibility of being pathogenic, for instance, the positive correlation between vitamin D and serum cholesterol and LDL. The same association has been previously reported by numerous studies including a report by Giri et al [30]. Grimes [31] has reported that in the absence of sunlight the inactive vitamin D is diverted to the synthesis of cholesterol.…”
Section: Discussionsupporting
confidence: 84%